2019
DOI: 10.1002/joa3.12193
|View full text |Cite
|
Sign up to set email alerts
|

Permanent junctional reciprocating tachycardia in infants and Children

Abstract: Permanent junctional reciprocating tachycardia ( PJRT ) is a rare form of supraventricular tachycardia ( SVT ). It generally presents in infants but can be difficult to diagnose. The characteristic EKG findings, response to Adenosine and persistence or frequent recurrences are helpful in making the diagnosis. It is usually difficult to manage with the initial and single medications used in SVT . Many patients are misdia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 30 publications
0
29
0
2
Order By: Relevance
“…However, if the tachycardia does not resolve with medical treatment, catheter ablation procedures may be required as an alternative option. 2,4,6,13,14 In this specific case, although tachycardia was resolved completely on the sixth day of life without further need of the catheter ablation procedure in the patient, he then died due to septic shock. Intravenous adenosine is recommended as the first choice of treatment to terminate hemodynamically stable acute episodes of re-entrant SVT involving AV node.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…However, if the tachycardia does not resolve with medical treatment, catheter ablation procedures may be required as an alternative option. 2,4,6,13,14 In this specific case, although tachycardia was resolved completely on the sixth day of life without further need of the catheter ablation procedure in the patient, he then died due to septic shock. Intravenous adenosine is recommended as the first choice of treatment to terminate hemodynamically stable acute episodes of re-entrant SVT involving AV node.…”
Section: Discussionmentioning
confidence: 71%
“…2 12 Although earlier studies have stated that using a combination of amiodarone, digoxin, and verapamil is the most effective regimen, currently, a combination of flecainide and amiodarone has been reported to be slightly more successful in the treatment of PJRT and reversing cardiomyopathy. 2 In a study by Kang et al 3 antiarrhythmic medications were used for initial management in 76% of patients, while catheter ablation was used initially in only 10% of patients. They also reported that medications achieved clinical benefit in 64% of patients and complete resolution in 23% of patients, and 72% of all patients underwent catheter ablation procedures with a success rate of 90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De manera característica es incesante y las características electrocardiográficas son las de una taquicardia con complejos QRS estrechos, regulares, con un intervalo RP muy largo y uno PR normal, pero con un eje de la onda P anormal, a diferencia del sinusal. Por lo general es difícil de tratar con los fármacos iniciales; las bajas frecuencias cardíacas de la taquicardia rara vez producen síntomas, pero su carácter incesante puede desencadenar miocardiopatía arrítmica 46 .…”
Section: Taquicardia Recíproca De La Uniónunclassified